Enhancing the ride comfort of off-road vibratory rollers with seat suspension using optimal quasi-zero stiffness. (January 2023) - Ni, Dengke; Jiao, Renqiang; Nguyen, Vanliem; Zhang, Jianrun
The research proposes a new design of the seat suspension equipped with the quasi-zero stiffness (QZS) and hydraulic mount (HM) of the cab isolation system to improve the ride comfort of off-road vibratory rollers. To assess the ride comfort of the vehicle using the QZS and the HM, a dynamic model of the off-road vibratory roller is built and researched under various interactions of the drum/wheel and off-road terrain. Based on the multi-objective genetic algorithms, the design parameters of the QZS are also optimized to further enhance the vehicle's ride comfort. The QZS optimized (QZSO)'s efficiency and the ride comfort of the off-road vibratory roller are analyzed based on the indexes of the seat displacement and acceleration; and the cab's pitching and rolling acceleration. The experimental investigation is then carried out to verify the accuracy of the mathematical model and research result. The investigation result indicates that with the QZSO applied on the seat isolation, the Root-Mean-Square and Power-Spectral-Density of the acceleration responses of the seat and cab are greatly decreased compared to the seat isolation without the QZS in both the time and frequency regions. Particularly, the Root-Mean-Square acceleration of the seat is remarkably decreased by 61.7% when the vehicle is moving and 67.5% when the vehicle is working. Consequently, this research can provide a valuable reference and knowledge for the application of the QZSO on the driver's seat suspension of off-road vehicles to optimize ride comfort.